Mapping the global landscape of STEM education: a bibliometric analysis using Scopus database - Aboudahr, Shorouk; Aslam, Sarfraz; Hua, Lau Ung; Misron, Aervina; Raime, Sharfika; Bee Wah, Yap (Institute of Advanced Engineering and Science, 2024)
Global innovation, economic growth, and societal advancement require excellence in science, technology, engineering, and mathematics (STEM) education. This study performed a bibliometric examination of articles related to STEM in education. A bibliographic dataset indexed in the Scopus database from 1980 to 2023 was analyzed using Excel and VOSviewer software. A total of 2,595 publications were taken for analysis. Bibliometric analysis results indicate that there has been a consistent growth in publications related to STEM education, and the highest number of publications was in 2022. The top three contributors are authors from North America, Oceania, Europe, and Asia. The United States was the most active contributor to STEM publications and had connections with Australia and Turkey. The most prolific journal is the International Journal of STEM Education, which has garnered 2,588 citations. Keywords such as “STEM,” “STEM education,” “STEM,” and “Education computing” were frequently used in these articles. Consequently, by shedding light on specific gaps in the existing literature, a comprehensive analysis of STEM education could aid scholars and practitioners in advancing their current understanding of this field.